Trees and shrubs of native flora in green areas of the South-East coast of the Crimea - Potapenko, I L; Klimenko, N I; Letukhova, V Yu; Klimenko, O E (IOP conference series. Earth and environmental science, 2021)
The article examines species of native dendroflora in parks and other green areas of the South-Eastern coast of the Crimea. Those of them that are often used are considered, as well as rare one. The oldest woody aborigines in the parks of the region are identified, and their morphometric data are given. The work also considers neophytes of the Crimean flora (cedars, cypresses, pines), that emphasize the Mediterranean character of the local landscapes. Special attention we have paid to species with regional and state conservation status. Cultivating them in gardens and parks will serve as an additional measure to preserve them. We proposed species of native trees and shrubs with good ornamental properties and suitable for the soil and climatic conditions of the region. Thus, we expand their species diversity in cultural cenosis. Their physiognomic correspondence to local picturesque landscapes is important. Artificial green spaces play an important role in the conservation of biodiversity, as well as rare protected species of the Crimean flora. The preservation of artificial green zones should correspond with the general concept of nature protection in the region.